Atividade β-D-N-Acetilglucosaminidásica de enzimas imobilizadas extraídas da Artemia franciscana e possíveis aplicações biotecnológicas - Santos, Pablo de Castro (2008)
A β-D-N-acetilglucosaminidase extracted and partially isolated from crustacean Artemia franciscana by ammonium sulfate precipitation and filtration gel chromatography Bio Gel A 1.5m. the enzyme was immobilized on ferromagnetic Dacron yielding a insoluble active derivative with 5.0 units/mg protein and 10.35% of the soluble enzyme activity. β-D-N-acetilglucosaminidase-ferromagnetic Dacron was easily removed from the reaction mixture by a magnetic field, it was reused for ten times without loss in its activity. The ferromagnetic Dacron was better activated at pH 5.0. The particles visualized at scanning electron microscope (SEM) had presented different sizes, varying between 721nm and 100µm. Infra red confirmed immobilization on support, as showed by primary amino peaks at 1640 and 1560 cm-1 . The immobilize enzyme presented Km of 2.32 ± 0.48 mM and optimum temperature of 50°C. Bought presented the same thermal stable of the soluble enzyme and larger enzymatic activity at pH 5.5. β-D-N-acetilglucosaminidase-Dacron ferromagnético showed sensible for some íons as the silver (AgNO3), with loss of activity. The β-D-N acetilglucosaminidase activity for mercury chloride (HgCl2), whom is one of the most toxic substance joined in nature, it was presented activity already diminished at 0,01mM and lost total activity at 4mM, indicating sensitivity for this type of metal. β-D-N-acetilglucosaminidase-ferromagnetic Dacron showed degradative capacity on heparan sulfate, the enzyme still demonstrated degradative capacity on heparan sulphate, suggesting a possible application to produce fractions of this glycosaminoglycan